2015
DOI: 10.1037/scp0000083
|View full text |Cite
|
Sign up to set email alerts
|

Processes and outcomes of theistic spiritually oriented psychotherapy: A practice-based evidence investigation.

Abstract: Various approaches for incorporating spirituality into psychotherapy have been developed, but few have been submitted to empirical scrutiny. The present article reports the results of a practice-based evidence (PBE) study, and demonstrates the value of PBE as a research strategy for the empirical evaluation of spiritually oriented psychotherapies (SOPs). This approach involves examining the effectiveness of SOPs in routine settings, providing more externally valid results than randomized controlled trials. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Although the absence of a comparison group and manualized approach limits the ability to gauge whether these improvements can be attributed to specific therapeutic activities, this finding aligns with outcomes of controlled trials of SIPs (Anderson et al, 2015; Captari et al, 2018; Gonçalves et al, 2015). In addition, Sanders et al (2015) found the same pattern in a PBE study of SIPs conducted in a religiously affiliated university counseling center. On the other hand, we did not find corresponding improvements in representations of God.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Although the absence of a comparison group and manualized approach limits the ability to gauge whether these improvements can be attributed to specific therapeutic activities, this finding aligns with outcomes of controlled trials of SIPs (Anderson et al, 2015; Captari et al, 2018; Gonçalves et al, 2015). In addition, Sanders et al (2015) found the same pattern in a PBE study of SIPs conducted in a religiously affiliated university counseling center. On the other hand, we did not find corresponding improvements in representations of God.…”
Section: Discussionmentioning
confidence: 59%
“…In tandem, these findings perhaps suggest clinicians did not affirm trusting God with highly distressed clients in the initial alliance‐building phase but then implement this intervention more often when addressing more severe problems that possibly were not improving over the course of treatment. However, in keeping with Sanders et al (2015), the size of the client sample likely limited the ability to detect unique effects for other spiritual interventions.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In recent years, clinical psychology has rediscovered many of the helpful techniques and interventions that originated centuries ago from the great spiritual, religious, and wisdom traditions (e.g., Hood, Hill, & Spika, 2009;Pargament, 2007;Pargament, Exline, Jones, Mahoney, & Shafranske, 2013;Plante, 2009Plante, , 2016Sanders et al, 2015). Much has already been written about spirituality in clinical practice in recent years.…”
mentioning
confidence: 99%